A comparison of financial performance of Czech credit unions and European cooperative banks - Matěj Kuc; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2015)
Czech credit unions have been yet criticized by both academics and regulatory representatives for its business based on moral hazard and excessive risk taking. This paper empirically assesses financial performance of Czech credit unions in relation with other European cooperative banks in terms of profitability and stability. To do that, we created a unique dataset of 283 cooperative banks from 15 European countries in the 2006-2013 period. System GMM method is employed as a main instrument of our empirical analysis and alternative panel data methods are used as supplementary techniques. Results revealed poor performance of Czech credit unions in terms of both profitability and stability. Moreover, adverse trends in stability measures of Czech credit unions are in sharp contrast to the tendencies in the rest of cooperative banks in our sample. To conclude, we argue that bigger Czech credit unions will face serious financial problems in coming years.
Keywords: C23; G21; L25; 330; credit union; cooperative banking; financial statements; moral hazard; credit risk; system GMM; Z-score